Evaluation of toxicological implications of inhalation exposure to kerosene fumes and petrol fumes in rats - Uboh, Friday E. (Acta Biologica Szegediensis, 2005)
Toxicological implications of exposure to ungraded concentrations of kerosene and petrol fumes in albino Wistar rats were investigated after two weeks of 4 hours daily inhalation. Serum aminotransferases (AST and ALT), alkaline phosphatase (ALP), total cholesterol (Chol), triglyceride (TG) levels and histological analysis of the liver tissues were used as diagnostic markers to assess liver dysfunction. The mean levels of these markers determined for the group of rats exposed to kerosene and petrol fumes (test groups), as compared with the levels for the control group were significantly (p < 0.05) higher. ALT, AST and ALP levels of the kerosene exposed group were raised by 191%, 161% and 204% while serum total cholesterol and TG levels increased by 129% and 118%, respectively. The increases in the serum levels of AST, ALT, ALP, Chol, TG in the petrol exposed group were 177%, 140%, 191%, 100% and 97%, respectively, when compared with the controls. Histological analysis of the liver tissues of the experimental test groups indicated degenerative changes in the ultrastructural integrity of the hepatic cells. These results showed that frequent exposure to kerosene and petrol fumes may be highly deleterious to the liver cells.